2006
DOI: 10.1021/jp062020e
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Electronic and Nuclear Dynamics for Charge Transfer in 1-Ethyl-4-(carbomethoxy)pyridinium Iodide

Abstract: Although polaronic interactions and states abound in charge transfer processes and reactions, quantitative and separable determination of electronic and nuclear relaxation is still challenging. The present paper employs the amplitudes, polarizations, and phases of four-wave mixing signals to obtain unique dynamical information on relaxation processes following photoinduced charge transfer between iodide and 1-ethyl-4-(carbomethoxy)-pyridinium ions. Pump-probe signal amplitudes reveal the coherent coupling of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 93 publications
0
23
0
Order By: Relevance
“…Solute dynamics of ECMPI in methanol and acetonitrile have been previously characterized, where the electron-transfer rates were found to correlate with the acceptor-donor distance, and the charge transfer reaction was found to be nearly a factor of ten times faster in acetonitrile than in methanol. 55 Interestingly, PORS spectra for ECMPI in acetonitrile and methanol revealed that the polarizability spectral density was time-dependent ( Figure 6). The general trend observed in both solvents was that of an initial broadband inertial response followed by a decrease in the spectral density linewidth.…”
Section: Pors and Raptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Solute dynamics of ECMPI in methanol and acetonitrile have been previously characterized, where the electron-transfer rates were found to correlate with the acceptor-donor distance, and the charge transfer reaction was found to be nearly a factor of ten times faster in acetonitrile than in methanol. 55 Interestingly, PORS spectra for ECMPI in acetonitrile and methanol revealed that the polarizability spectral density was time-dependent ( Figure 6). The general trend observed in both solvents was that of an initial broadband inertial response followed by a decrease in the spectral density linewidth.…”
Section: Pors and Raptorsmentioning
confidence: 99%
“…50 Despite its success, variants of the formalism that consider anharmonicity of the liquid state potential [51][52][53] and additional electronic resonances in-/outside the laser bandwidth have been discussed. 54,55 Figure 2 shows 3-pulse PE peak shift (3 PEPS) vs. population time T data from IR144 for several different polar solvents: methanol, ethanol, butanol, and ethylene glycol. The 3PEPS data from IR144 in different solvents have common features.…”
Section: Pe Spectroscopiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The observable, however, is not the solute fluorescence, but a time-delayed 4-wave-mixing (effectively, an intermolecular vibrational) spectrum of the surrounding solvent. [11][12][13][14][15][16][17][18][19][20][21] In the resonantpump polarizability response spectra (RP-PORS) carried out by the Scherer group, for example ( Fig. 1), [15][16][17] a transientgrating spectrum is taken by crossing two non-resonant optical pulses in the sample a time T after the initial resonant solute excitation, and then watching the light scattering from another non-resonant optical pulse a time t after that.…”
Section: Introductionmentioning
confidence: 99%
“…24,25,35 Our previous design employed heterodyne detection to separate real and imaginary signal components but did not fully resolve the signal phase. 36,37 Therefore, the PORS signals are dominated by motions of the solvent that are coupled to/driven by the charge transfer reaction; these are the dynamics PORS is designed to measure. In addition, the Raman probe measurement is performed in the frequency domain with fixed pulse delays, as in the FSRS, [30][31][32][33][34] to speed up data acquisition by about 300-fold.…”
Section: Introductionmentioning
confidence: 99%